Proceedings of the 3rd Workshop on Evaluating Vector Space Representations For 2019
DOI: 10.18653/v1/w19-2011
|View full text |Cite
|
Sign up to set email alerts
|

Probing Biomedical Embeddings from Language Models

Abstract: Contextualized word embeddings derived from pre-trained language models (LMs) show significant improvements on downstream NLP tasks. Pre-training on domain-specific corpora, such as biomedical articles, further improves their performance. In this paper, we conduct probing experiments to determine what additional information is carried intrinsically by the in-domain trained contextualized embeddings. For this we use the pre-trained LMs as fixed feature extractors and restrict the downstream task models to not h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 29 publications
1
84
0
Order By: Relevance
“…ESIM with BioELMo: Following the state-ofthe-art recurrent architecture of NLI (Peters et al, 2018), we use pre-trained biomedical contextualized embeddings BioELMo (Jin et al, 2019) for word representations. Then we apply the ESIM model (Chen et al, 2016), where a biLSTM is used to encode the question and context/long answer, followed by an attentional local inference layer and a biLSTM inference composition layer.…”
Section: Bilstmmentioning
confidence: 99%
“…ESIM with BioELMo: Following the state-ofthe-art recurrent architecture of NLI (Peters et al, 2018), we use pre-trained biomedical contextualized embeddings BioELMo (Jin et al, 2019) for word representations. Then we apply the ESIM model (Chen et al, 2016), where a biLSTM is used to encode the question and context/long answer, followed by an attentional local inference layer and a biLSTM inference composition layer.…”
Section: Bilstmmentioning
confidence: 99%
“…Accuracy fastText 68.7% GloVe 73.1% BioELM o (Jin et al, 2019) 78.2% ESIM w/K Romanov and Shivade (2018). Adding knowledge graph information to the base models showed an absolute improvement of 4.97% in case of fastText and 1.36% in case of GloVe.…”
Section: Modelmentioning
confidence: 99%
“…Adding knowledge graph information to the base models showed an absolute improvement of 4.97% in case of fastText and 1.36% in case of GloVe. The baseline model utilizing BioELMo as base embeddings (Jin et al, 2019) showed an accuracy of 78.2%. On adding knowledge graph information, we were able to improve these results to 78.76% and on further addition of sentiment information, the accuracy rose to 79.04%…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations